EVALUASI PERATURAN DAERAH NOMOR 8 TAHUN 2012 TENTANG RETRIBUSI IZIN GANGGUAN (STUDI KASUS PABRIK KARET PT. BANGKINANG TAHUN 2015) - Wahyudi, Mohd. Fadli; Yuliani, Febry (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The establishment of these places of business must have a disturbance permit (HO). It aims to provide protection to the entrepreneurs and the surrounding community, as an effort to prevent environmental pollution, conservation of natural resources and the environment as well as income of Original Regional Income. Pekanbaru Municipal Government has issued Local Regulation No. 8 of 2012 on the Distribution License Permit which one of its objects is the rubber factory of PT. Bangkinang which has been operating near the settlement community Jl. Taskurun Kota Pekanbaru. The purpose of this study is to find out how the Evaluation of Local Regulation No. 8 of 2012 on Retribution License Nuisance (case study of rubber factory of PT Bangkinang Year 2015) and what factors become the influence in Evaluation of Local Regulation. This research uses qualitative research methods with descriptive research type, which can be interpreted as problem-solving process investigated by describing the state of the research subject based on the facts that appear during the study which then continued with based on the existing theories.Based on the results of research can be concluded that the Regional Regulation of Pekanbaru City No. 8 of 2012 About Distribution License Nuisance has accommodated the granting of licensing disruption to all existing businesses in Pekanbaru City is no exception rubber factory PT. Bangkinang who must have permission to interfere with previously conducted AMDAL research. Factors influencing the evaluation of Pekanbaru Municipal Regulation No. 8/2012 on License Distribution License are as follows: human resources, communication and weak law enforcement on regional regulationsKeywords: Evaluation, Policy, Levy